The technological innovation and its effect on operation efficiency of the oil and gas sector of the United Arab Emirates - Al Hosani, Waleed Mohamed Salem Mohamed (Tanjong Malim, 2024)
The technological innovation and its effect on operation efficiency of the oil and gas sector of the United Arab Emirates by Al Hosani, Waleed Mohamed Salem Mohamed